2022
DOI: 10.1155/2022/2751559
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Magnetic Resonance Imaging in Diagnosing Placenta Accreta: A Systematic Review and Meta-Analysis

Abstract: Background. The disease burden and incidence of placenta accreta are increasing worldwide. The morbidity and mortality associated with undiagnosed placenta accreta are both high, highlighting the important of early diagnosis and intervention. In recent years, increasing studies are exploring the diagnostic value of magnetic resonance imaging (MRI) for placenta accreta. Compared with traditional ultrasound, MRI has the advantages of high-resolution, multiangle imaging, and less influence by amniotic fluid and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The effect of P fertilizer application was considered significant if the 95% CI did not overlap with zero; otherwise, no significant effect was deemed to exist. Egger's test and funnel plots are the main methods for testing the quality of metaanalyses and their reliability was confirmed by the previous literature [28,29]. To evaluate the quality of the meta-analysis, the Egger's test (Table S1) and funnel plot (Figures S1-S3) were used in this paper.…”
Section: Discussionmentioning
confidence: 74%
“…The effect of P fertilizer application was considered significant if the 95% CI did not overlap with zero; otherwise, no significant effect was deemed to exist. Egger's test and funnel plots are the main methods for testing the quality of metaanalyses and their reliability was confirmed by the previous literature [28,29]. To evaluate the quality of the meta-analysis, the Egger's test (Table S1) and funnel plot (Figures S1-S3) were used in this paper.…”
Section: Discussionmentioning
confidence: 74%
“…In a recent investigation, Huien Lin et al [ 17 ] analyzed 10 primary studies, comprising 4 retrospective and 6 prospective studies, revealing a magnetic resonance imaging (MRI) diagnostic sensitivity and specificity for placenta implantation of 88% and 79%, respectively. Nevertheless, our experimental findings notably surpass these figures.…”
Section: Discussionmentioning
confidence: 99%
“…PAS is actually increasing in the entire world due to the increasing rate of cesarean deliveries, placenta previa, and ART (assisted reproductive technology). 5 , 34 However, there are many studies on the risk factors of PAS. Wu et al 35 used the logistic regression (LR) model to analyze 64,359 cases of delivery from 1982 to 2002 according to the statistics of the University of Chicago, and it was early found that placenta previa and multiple cesarean sections are the main risk factors of PAS.…”
Section: Epidemiology and Risk Factors For Placenta Accreta Spectrummentioning
confidence: 99%